1994
DOI: 10.1038/hdy.1994.95
|View full text |Cite
|
Sign up to set email alerts
|

Allopolyploid vs. autopolyploid origins in the genus Lathyrus (Leguminosae)

Abstract: Allopolyploid vs. autopolyploid origins of polyploid species of the genus Lathyrus have been tested by the C-banding technique and electrophoretical procedures for 11 genetic loci belonging to six isozyme systems. Results of both experiments suggest for the polyploid populations of L. palustris and L. pratensis an autopolyploid origin from their respective diploid counterparts. Nevertheless, L. venosus seems to have originated through allopolyploidy involving two sympatric diploid species, L. ochroleucus and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Although polyploidy is considered as one of the main mechanisms of evolution and diversification in plants (Soltis and Soltis 1999), it is a rare phenomenon in the genus Lathyrus (Senn 1938;Yamamoto et al 1984;Gutiérrez et al 1994). The finding of triploid and tetraploid individuals in L. nervosus constitutes the first report of polyploidy for the section Notolathyrus, whereas the existence of uneven polyploidy and a mixed population with three different cytotypes are novelties for the genus.…”
Section: Autopolyploidy In the Section Notolathyrusmentioning
confidence: 96%
See 2 more Smart Citations
“…Although polyploidy is considered as one of the main mechanisms of evolution and diversification in plants (Soltis and Soltis 1999), it is a rare phenomenon in the genus Lathyrus (Senn 1938;Yamamoto et al 1984;Gutiérrez et al 1994). The finding of triploid and tetraploid individuals in L. nervosus constitutes the first report of polyploidy for the section Notolathyrus, whereas the existence of uneven polyploidy and a mixed population with three different cytotypes are novelties for the genus.…”
Section: Autopolyploidy In the Section Notolathyrusmentioning
confidence: 96%
“…The extensive similarity observed in the chromosome morphology, the banding pattern and the mapping of rDNA loci between the additional complements of the polyploid individuals and those of the diploid ones belonging to the same population strongly suggests that 3x and 4x cytotypes may have originated by autopolyploidy. Although interpopulation cytotype polymorphisms in L. palustris and L. pratensis were considered as cases of autopolyploidy (Gutiérrez et al 1994), and allopolyploidy has been suggested for L. venosus (Khawaja et al 1997(Khawaja et al , 1998, the mechanism by which polyploidization occurred in the genus has not been considered yet. In general, it is proposed that polyploids may be formed by somatic chromosome doubling or by sexual polyploidization (Darlington 1965;Harlan and De Wet 1975).…”
Section: Autopolyploidy In the Section Notolathyrusmentioning
confidence: 98%
See 1 more Smart Citation
“…Using different cytogenetics data and isozymatic analysis, GUTIERREZ et al (1994) differentiated allopolyploid and autopolyploid origin of different Lathyrus species. Different morphological and cytological parameters indicated autopolyploid origin of present tetraploid plants which can be further confi rmed by studying tetrasomic inheritance pattern of different isozyme markers in the present material as suggested by SOLTIS et al, (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between an auto-and allopolyploid origin of a polyploid lineage has hitherto required detailed cytogenetic analysis. Such work included the extraction and staining of metaphasic chromosomes in order to characterize chromosomal configurations, such as the telomeric heterochromatin in the long arm (Tymowska and Fischberg 1982;Chalup et al 2012), and cluster analysis to test whether each of the homeologous chromosomes group together as expected under autopolyploidy (Gutiérrez et al 1994). Despite improvements in the acquisition of molecular markers, the rational beyond this test has more or less remained unchanged, with auto-versus allopolyploid origins still distinguished by testing for the occurrence of divergent chromosomes within the same tetraploid cytotype, even where data from parental species are not available (Mráz et al 2012).…”
Section: Distinguishing Between Allo-and Autopolyploidisationmentioning
confidence: 99%